Priorities, solidarity and the watering can: research policies and conceptions of relevance in a Latin American traditional university setting - Vasen, Federico (2012)
This paper presents an analysis of institutional policies for the promotion of research activities in Argentina´s largest higher education institution: the University of Buenos Aires (UBA). Procedures for priority setting and their integration in university governance are discussed. In addition, the theoretical roots of each policy initiative are analyzed and described in relation to the different conceptions of relevance that a science policy may adopt and the suppositions about university-society relationships that may be identified in them. The case suggests that although policymakers intended to develop strategic research initiatives, both the lack of external knowledge demands and academic culture of researchers of following their own agenda, ensured that these attempts ended up in failure. Only a large external event such as the deep economic crisis of 2001 resulted in innovative "social urgency" projects and a move towards greater institutional social commitment.